Evaluación de la sustentabilidad de cinco unidades productivas de cacao (Theobroma cacao L.) en el cantón Mocache de la provincia de los Ríos - Olivo Gamarra, Genesis Dagmar (2022)
The production of the cocoa crop is currently not considered sustainable for most agricultures and satisfies the demand for food, it has been affected by various situations associated with climate change and productive factors. This is why the agriculture of this time must be an agriculture that implements new agricultural practices that achieve the production of food in greater quantity and quality without affecting the environment.